Detection Methods and Clinical Applications of Circulating Tumor Cells in Breast Cancer - Zhang, Hongyi; Lin, Xiaoyan; Huang, Yuan; Wang, Minghong; Cen, Chunmei; Tang, Shasha; Dique, Marcia R.; Cai, Lu; Luis, Manuel A.; Smollar, Jillian; Wan, Yuan; Cai, Fengfeng (Frontiers in Oncology, 2021)
Circulating Tumor Cells (CTCs) are cancer cells that split away from the primary tumor and appear in the circulatory system as singular units or clusters, which was first reported by Dr. Thomas Ashworth in 1869. CTCs migrate and implantation occurs at a new site, in a process commonly known as tumor metastasis. In the case of breast cancer, the tumor cells often migrate into locations such as the lungs, brain, and bones, even during the early stages, and this is a notable characteristic of breast cancer. Survival rates have increased significantly over the past few decades because of progress made in radiology and tissue biopsy, making early detection and diagnosis of breast cancer possible. However, liquid biopsy, particularly that involving the collection of CTCs, is a non-invasive method to detect tumor cells in the circulatory system, which can be easily isolated from human plasma, serum, and other body fluids. Compared to traditional tissue biopsies, fluid sample collection has the advantages of being readily available and more acceptable to the patient. It can also detect tumor cells in blood earlier and in smaller numbers, possibly allowing for diagnosis prior to any tumor detection using imaging methods. Because of the scarcity of CTCs circulating in blood vessels (only a few CTCs among billions of erythrocytes and leukocytes), thorough but accurate detection methods are particularly important for further clinical applications.